2021
DOI: 10.1016/j.bbih.2021.100332
|View full text |Cite
|
Sign up to set email alerts
|

Psychoneuroimmunology in the context of perinatal depression - Tools for improved clinical practice

Abstract: Maternal mental health spans in a temporary manner from pre-conception through the phases of pregnancy, childbirth, and the postpartum period (i.e., perinatal). The psychoneuroimmunology (PNI) field has made important contributions to the knowledge of the pathophysiology of poor perinatal mental health, but the PNI lens could be used more broadly to inform clinical practice. This review argues that PNI holds the key to several important aspects of variations in mental health for pregnant and postpartum women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Physiological and emotional challenges inherent to pregnancy and childbirth, such as substantial changes in hormone levels, alterations in the cardiovascular and immune systems [ 1 , 2 ], and concerns about impending parenthood, can reveal psychiatric vulnerability in many women, potentially culminating in perinatal affective disorders [ 3 – 7 ]. An estimated 10–20% of women suffer from postpartum depression (PPD [ 6 , 8 ]); and 20% of women meet the criteria for at least one anxiety disorder during pregnancy and the postpartum period [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological and emotional challenges inherent to pregnancy and childbirth, such as substantial changes in hormone levels, alterations in the cardiovascular and immune systems [ 1 , 2 ], and concerns about impending parenthood, can reveal psychiatric vulnerability in many women, potentially culminating in perinatal affective disorders [ 3 – 7 ]. An estimated 10–20% of women suffer from postpartum depression (PPD [ 6 , 8 ]); and 20% of women meet the criteria for at least one anxiety disorder during pregnancy and the postpartum period [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was argued that this approach can more clearly establish whether immune dysfunction is present prior to symptom onset, which may improve prediction of postpartum associated illness. The use of objective measures, such as biomarkers, was identified as an important tool to help identify women at risk for postpartum depression ( Fransson, 2021 ) . In line with these suggestions, Szpunar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mental health not only impacts the health of the mother, but it can also have long lasting implications for infant and child development [8][9][10][11][12]. In the past 30 years, a substantial body of evidence is building on Barker's theory of the developmental origin of health and disease (DoHD) which demonstrated that adverse maternal conditions, such as stress during the first 1000 days of life can increase the risk of metabolic, immunologic, and neurobehavioral disorders in offspring [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%